2012
DOI: 10.3390/polym4021259
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic Synthesis and Chemical Recycling of Novel Polyester-Type Thermoplastic Elastomers

Abstract: Novel polyester-type thermoplastic elastomers based on poly(alkylene succinate)s were synthesized by the lipase-catalyzed copolymerization of cyclic diol/succinate oligomer and cyclic diol/alkylthiosuccinate oligomer. These copolymers exhibited biodegradabilities by activated sludge and a wide range of thermal and mechanical properties that were dependent on the molecular structure and the content of side alkylthio groups. The degree of crystallinity of the copolymer decreased with increasing content of alkylt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 25 publications
1
16
0
Order By: Relevance
“…The application of the ROP method to the synthesis of PBS was reported for the first time by Japanese researchers using as the feed a mixture of cyclic butylene succinate oligomers that were either synthesized by enzymatic cyclization [30][31][32] or recovered as a subproduct in the preparation of PBS by melt polycondensation. 33 On the other hand, the first papers reporting the synthesis of PBF homopolyesters by ROP were published at the end of last year, 34,35 and the first work using ROP for the preparation of PBF copolyesters has just been published; in that work a series of poly(butylene furandicarboxylate-co-terephthalate) copolyesters was synthesized and their properties evaluated as a function of the comonomer composition.…”
mentioning
confidence: 99%
“…The application of the ROP method to the synthesis of PBS was reported for the first time by Japanese researchers using as the feed a mixture of cyclic butylene succinate oligomers that were either synthesized by enzymatic cyclization [30][31][32] or recovered as a subproduct in the preparation of PBS by melt polycondensation. 33 On the other hand, the first papers reporting the synthesis of PBF homopolyesters by ROP were published at the end of last year, 34,35 and the first work using ROP for the preparation of PBF copolyesters has just been published; in that work a series of poly(butylene furandicarboxylate-co-terephthalate) copolyesters was synthesized and their properties evaluated as a function of the comonomer composition.…”
mentioning
confidence: 99%
“…In fact, depolymerisation exclusively yielded cyclic oligomers, suggesting that identical yields could be reached for a second polymerization . Yagihara and Matsumura also demonstrated the recyclability of thermoplastic elastomers after using CALB for the copolymerization of diols and succinate monomers . They recovered identical molecular weights after recycling.…”
Section: Recent Erop Techniques and Architectures Using Calbmentioning
confidence: 92%
“…[130] Yagihara and Matsumura also demonstrated the recyclability of thermoplastic elastomers after using CALB for the copolymerization of diols and succinate monomers. [131] They recovered identical molecular weights after recycling. In recent years, other research groups have demonstrated the enzymatic recyclability of polymers by reactive extrusion [132] and ring-chain equilibria.…”
Section: Microwave Radiation (Mwr)mentioning
confidence: 95%
“…The substrate concentration in as olvent is an important parameter for an enzymatic process because al ow substrate content may lead to the cyclization of oligomers to form macrocycles, [244,245] Reviews et al [249] determined that 350 wt %o fd iphenyl ether (vs. total mass of monomers) was optimal for the transesterification of bis(2,2,2-triflurorethyl) sebacate with 1,4-BDOa t3 7 8Cb yt he crude R. miehei lipase. Jiang et al showed that 150 wt %o fd iphenyle ther was the optimal solventa mount for the N435catalyzed transesterification reactiono fd iethyl succinate, dimethyl itaconate, and 1,4-BDO in diphenyl ether at 80 8C.…”
Section: Influence Of the Amountofsolventmentioning
confidence: 99%
“…The substrate concentration in as olvent is an important parameter for an enzymatic process because al ow substrate content may lead to the cyclization of oligomers to form macrocycles, [244,245] and the final molar mass can be decreased if the optimal conditions are not applied. As some examples,L inko ChemSusChem 2018, 11,3836 -3870 www.chemsuschem.org et al [249] determined that 350 wt %o fd iphenyl ether (vs. total mass of monomers) was optimal for the transesterification of bis(2,2,2-triflurorethyl) sebacate with 1,4-BDOa t3 7 8Cb yt he crude R. miehei lipase.…”
Section: Influence Of the Amountofsolventmentioning
confidence: 99%